Penelitian Berbahan Dasar Semen dan Kain untuk Elemen Interior - Nico Maximillian Joses; Andereas Pandu Setiawan; Jean Francois Poillot (Intra, 2019)
Researchers wanted to find alternative materials other than wood because of the very high use of wood which if possible the supply of wood in Indonesia would run out in a few years if not preserved. In this design, research began to research and look for information relating to unused fabrics, such as strengths, weaknesses, how to process, and so on by experimenting with fabrics and also cement. With these information, researchers began to make experimental design concepts and from the concept created a design that is a flower pot and a light sleeper.